AI-driven digital facilitator for personalized post-course support of educators - Nurbekova, Zhanat; Sembayev, Talgat; Zhetpisbayeva, Meiramgul; Baigusheva, Kanagat (International Journal of Innovative Research and Scientific Studies, 2025)
The current article aims to study the approaches and technologies for post-course support of teachers in the context of a new paradigm of continuous professional development. In a dynamically changing world, post-course support plays a significant role in ensuring sustainable professional development. This article proposes an innovative solution a digital personalized facilitator support for the post-course professional development period of teachers. The study employed a quantitative method with a sample size of 21,681 teachers to determine their educational needs, the use of AI, and the conditions for effective post-course support. About half of the respondents (40%) highlighted the importance of post-course support from coaches, colleagues, and administration, while more participants (75%) identified the need for AI tools for personalized professional development. The significance of the results is associated with the justification of an innovative solution to the problems of post-course support for teachers in the form of a patentable utility model of a digital facilitator. Its applicability as a facilitator in group sessions that monitor participants’ actions shows the prospects for its implementation in other areas of the teacher’s activity.